2020
DOI: 10.15586/qas.v12isp1.776
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the growth rate of Listeria innocua influenced by coriander seed essential oil and storage temperature in meat using FTIR

Abstract: The use of natural compounds to preserve food and the application of new tools for monitoring food safety is of great interest. In this study, the growth rate, including the lag time of Listeria innocua in ground lamb as a function of storage temperature (4, 10, 25, and 37°C) influence of the coriander seed essential oil (CEO), as an antimicrobial agent, was modeled. Fourier-transform infrared (FTIR) spectroscopy was used to monitor chemical changes in investigated specimens that may indicate spoilage in groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The samples coated by CEO‐loaded LPSM had significantly higher hardness value compared with the control sample, at the 7th day of storage. This could probably due to microbial growth‐suppression and meat enzymes activity‐inhibitory effects of the CEO and edible coating, thereby preventing meat protein degradation and subsequent pH increase and texture loss (Mohan et al., 2012; Omidi‐Mirzaei et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The samples coated by CEO‐loaded LPSM had significantly higher hardness value compared with the control sample, at the 7th day of storage. This could probably due to microbial growth‐suppression and meat enzymes activity‐inhibitory effects of the CEO and edible coating, thereby preventing meat protein degradation and subsequent pH increase and texture loss (Mohan et al., 2012; Omidi‐Mirzaei et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Frequencies of 1600-1640 and 1670-1680 cm −1 denoted β-sheet; while frequencies of 1640-1650 cm −1 represented random coils; and frequencies of 1650-1660 cm −1 , 1660-1670, and 1680-1700 cm −1 denoted α-helix and β-turn, respectively (Marzieh et al, 2020). The results showed that the major protein fractions had β-sheet (49.08-64.59%) and β-turn (29.80 and 43.68%) structures, followed by random coils (5.59 and 7.23%) and minor portions of α-helix.…”
Section: Macromolecular Interactions and Secondary Protein Fractions ...mentioning
confidence: 99%
“…In addition, an edible coating is also defined as key packaging material made using fruit can keep more nutrients, increasing antioxidation ability from edible components Carolina et al, 2014; da Silva et al, 2019; Torres‐León et al, 2018). Edible and natural coatings are applied to food to act as a barrier to the environment, hence decreasing microbes, water, and oxygen exposure (Omidi‐Mirzaei et al, 2020; Phothiset & Charoenrein, 2007). In addition, it has been reported that polysaccharides coating such as pectin or gums on food can keep moisture, while aiding in surface water removal and avoiding firm texture in the end food product after drying (Jafari et al, 2018; Lyu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%